A Quality-Improving Method for APT-Type NOAA Meteorological Satellite Signals - Mezei, Mate-Marton; Polgar, Zsolt Alfred (International Symposium on Electronics and Telecommunications (Online), 2024)
The Automatic Picture Transmission (APT) analog technology is still utilized on certain weather satellites, such as the NOAA polar-orbiting satellites, to transmit weather images in visible and infrared light. Like any satellite transmission, the APT transmission is influenced by the considerable distance between the satellite and the receiver, as well as the shadowing caused by the surroundings. Due to these factors, the SNR of the received signal may be low, necessitating the use of denoising techniques to enhance the quality of the decoded image. The paper proposes a denoising solution based on a smoothing technique, which is implemented at the demodulation process level, unlike other solutions that process the decoded image. Computer simulations were conducted to showcase the efficacy of the proposed solution. The simulations demonstrated that even a simple moving-average-based smoothing technique yields excellent results, making the solution suitable for basic APT receivers.